O PAMPA REVISITADO: EM DIA COM ALCIDES MAYA - Masina, Léa (Organon, 2004)
Almost a hundred years later, this present work celebrates the reediting of Alcides Maya’s literaryproduction. As a writer, Alcides Maya represents the Brazilian literature and that of Rio Grande do Sul State. As anauthor of fictional books, he also had a militant participation in the press and was one of the first literary critics inRio Grande do Sul. As a narrator, Alcides Maya brought the influences of the Rio Platense cultures into theBrazilian literature. In his critical rendering, Maya announced the European culture, being faithful to the nationalistproject on promoting Brazil’s intellectual growth. As it reads in his literary work, Maya was a comparatist “avant lalettre” who performed the role of an intercultural mediator. The importance of his work lies on the updated issuesthat he dealt with, as violence in the countryside and the land issue.